Impact of Multidrug-Resistant Pseudomonas aeruginosa Bacteremia on Patient Outcomes - Tam, Vincent H. (American Society for Microbiology (ASM), 2010)
Trends of rising rates of resistance in Pseudomonas aeruginosa make selection of appropriate empirical therapy increasingly difficult, but whether multidrug-resistant (MDR) P. aeruginosa is associated with worse clinical outcomes is not well established. The objective of this study was to determine the impact of MDR (resistance to three or more classes of antipseudomonal agents) P. aeruginosa bacteremia on patient outcomes. We performed a retrospective cohort study of adult patients with P. aeruginosa bacteremia from 2005 to 2008. Patients were identified by the microbiology laboratory database, and pertinent clinical data were collected. Logistic regression was used to explore independent risk factors for 30-day mortality. Classification and regression tree analysis was used to determine threshold breakpoints for continuous variables. Kaplan-Meier survival analysis was used to compare time to mortality, after normalization of the patients' underlying risks by propensity scoring. A total of 109 bacteremia episodes were identified; 25 episodes (22.9%) were caused by MDR P. aeruginosa. Patients with MDR P. aeruginosa bacteremia were more likely to receive inappropriate empirical therapy (44.0% and 6.0%, respectively; P < 0.001) and had longer prior hospital stays (32.6 ± 37.3 and 14.4 ± 43.6 days, respectively; P = 0.046). Multivariate regression revealed that 30-day mortality was associated with multidrug resistance (odds ratio [OR], 6.8; 95% confidence interval [CI], 1.9 to 24.0), immunosuppression (OR, 5.0; 95% CI, 1.4 to 17.5), and an APACHE II score of ≥22 (OR, 29.0; 95% CI, 5.0 to 168.2). Time to mortality was also shorter in the MDR cohort (P = 0.011). Multidrug resistance is a significant risk factor for 30-day mortality in patients with P. aeruginosa bacteremia; efforts to curb the spread of MDR P. aeruginosa could be beneficial.